Fractographic Analysis of Hardox Steels Research in the Field of High-Cycle Fatigue Regime - Pawel Szataniak; Magdalena Mazur; Robert Ulewicz; Frantisek Novy (Communications - Scientific letters of the University of Zilina, 2016)
The article presents preliminary fatigue tests results of two high-strength steels used in structural elements of trailers, wagons, farm devices, etc. Paper presents an analysis of fatigue test results of high-strength steels in the range from 104 to 107 numbers of cycles of applied load with a frequency of 40 Hz. Wöhler curve shows the results of the fatigue properties of steels Hardox 400 and Hardox 450, which are used in the construction of vehicles. Fatigue fractures were subjected to fractographic analysis in order to determine the mechanism of fatigue crack propagation.